Implementation of public health practices in tribal populations of India: challenges and remedies - Saurabh Rambiharilal Shrivastava; Prateek Saurabh Shrivastava; Jegadeesh Ramasamy (PAGEPress Publications, 2013)
Large inequities in health exist between indigenous and non-indigenous populations worldwide. This health divide has also been demonstrated in India, where indigenous groups are officially classified as scheduled tribes (STs). India has one of the largest tribal populations in the world. Tribal communities in general and primitive tribal groups in particular are highly disease prone and their misery is compounded by poverty, illiteracy, ignorance of causes of diseases, hostile environment, poor sanitation, lack of safe drinking water, blind beliefs, etc. As per the estimates of National Family Health Survey-3 (NFHS-3), the likelihood of having received care from a doctor is lowest for ST mothers (only 32.8% compared to India of 50.2%). While many strategies have been attempted over the years to discuss some of the economic, social, and physical factors preventing tribal population to get access to healthcare services, the ultimate outcome has remained far less than the expectations. Considering that these ST groups are culturally and economically heterogeneous, the methods to tackle their health problems should not only be integrated and multi-fold, but also specific to the individual groups as feasibly as possible. Measures like strengthening of the existing human resources, bringing health services within the reach of remote populations, promotion of health awareness, facilitation of community participation using innovative strategies, bringing about a change in the behavior of health care providers, implementation of measures for the empowerment of ethnic groups by carrying out administrative reforms and finally by ensuring the sustainability of all above recommended measures.